Optimising Wastewater Treatment: Acinetobacter sp. IrC1 As a Potential Multi-Resistant Bacterium for Copper Accumulation and Dyes Decolourisation - Wahyu Irawati; Triwibowo Yuwono; Reinhard Pinontoan; Valentine Lindarto (Tropical Life Sciences Research, 2023)
Improper disposal of waste containing copper and dye is an environmental issue that must be resolved immediately due to its harmful, non-degradable and toxic properties. Bioremediation efficiency can improve by cultivating copper and dye multi-resistant bacteria to remove various pollutant types simultaneously. This study aims at establishing the multi-resistance of Acinetobacter sp. IrC1 to copper and dyes. The effects of copper concentration on growth were determined using a spectrophotometer, while accumulation was analysed using an atomic absorption spectrophotometer. Bacteria-mediated dye decolourisation dyes were observed based on clear zone formation around bacterial colonies, while decolourisation percentage was calculated using a spectrophotometer. Results demonstrate that Acinetobacter sp. IrC1 resisted up to 8 mM CuSO4 and accumulated up to 292.93 mg/g dry weight of copper cells. Acinetobacter sp. IrC1 isolates were also resistant to 500 ppm Methylene Blue, Malachite Green, Congo Red, Mordant Orange, Reactive Black, Direct Yellow, Reactive Orange, Remazol, Wantex Red and Wantex Yellow dye, successfully removing up to 68.35% and 79.50% Methylene Blue and Basic Fuchsine in a medium containing 3 mM CuSO4, respectively. Further investigations are required to analyse the genetic composition of multi-resistant bacteria to optimise the effectiveness of indigenous bacterial isolates as bioremediation agents.